Answer:
0.44 (44%) of the students are boys.
Step-by-step explanation:
Hope this helps!
✧◝(⁰▿⁰)◜✧
Given inequality -3(4-6x) < x+5.
We have -3 in front of Parenthesis.
That represents multiplication of -3 and Parenthesis.
The multiplication of Parenthesis could be done by applying distributive property.
On distributing, we get
-12+18x < x+5
x is added on right side of the inequality. The reverse operation of addition is subtraction. So we need to subtract x from both sides, we get
-12+18x-x < x-x+5
-12+17x < 5
Now, we need to get rid -12 from left side.
So, we need to apply addition property of equality, we need to add 12 on both sides, we get
-12+12+18x < x+5+12
17x < 17
We need to get rid 17 from left side. So we need to apply division property of equality.
On dividing both sides by 17, we get
17x/17 < 17/17
x<1.
so for A it is 16 times as large because the area is 3*3 which is 9 but since it is a triangle the area is halved and is 4.5 and divide 72 by 4.5 which gives us 16
then for b I believe that the scale factor is 4
and for C it is asking for the bottom side of the scaled copy not of triangle A and 4*3=12 so the bottom is 12
ok now its complete =)
<span>Look
for the sum of 56 and 64, written as the product of its GCF and another sum.
First, let’s find the greatest common factor of both given numbers:
=> 56 = 1, 2, 4, 7, 8, 13, 28 and 56
=> 64 = 1, 2, 4, 8, 16, 32, and 64
Now, we need to find the greatest common factor between the two numbers. The GCF
of the 2 numbers is 8.
=> 56 / 8 = 7
=> 64 / 8 = 8
=> 56 + 64 = 120
=> (8 x 7) + (8 x 8)
=> 56 + 64
=> 120.</span><span>
</span>
Answer:
the third one
Step-by-step explanation: